2015
DOI: 10.1016/j.jjcc.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased extent of myocardial fibrosis in genotyped hypertrophic cardiomyopathy with ventricular tachyarrhythmias

Abstract: These results demonstrate that myocardial fibrosis determined by CMR imaging may be increased in genotyped HCM patients with episodes of VT/VF. A further prospective study will be needed to clarify the association between the LGE extent and arrhythmic events in HCM patients harboring sarcomere gene mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
10
0
2
Order By: Relevance
“…Most of the research focused on the comparison of different phenotypes and prognosis caused by different genetic mutations in HCM 3,30,31 , or the difference between the HCM patients and genetic carriers with negative phenotype 3234 . There were reports that described a single site mutation in the MYH7 gene producing not only a classic hypertrophic pattern but also a RCM phenotype 35–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research focused on the comparison of different phenotypes and prognosis caused by different genetic mutations in HCM 3,30,31 , or the difference between the HCM patients and genetic carriers with negative phenotype 3234 . There were reports that described a single site mutation in the MYH7 gene producing not only a classic hypertrophic pattern but also a RCM phenotype 35–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have demonstrated an association between the extent of LGE and presence of NSVT, whereas others have found an association between the presence rather than the extent of LGE and NSVT . Furthermore, other studies have found a correlation between the extent of LGE and inducible ventricular tachycardia (VT) and the origin of ventricular arrhythmia to be within the myocardium exhibiting LGE . Despite the lack of strong evidence, a higher burden of NSVT as well as more prolonged and faster runs of NSVT are considered by many clinicians to be a marker of greater arrhythmia risk.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple studies have found LGE to be independently associated with NSVT in HCM. 1 Some of these studies have demonstrated an association between the extent of LGE and presence of NSVT, [2][3][4][5][6][7][8][9][10][11][12] whereas others have found an association between the presence rather than the extent of LGE and NSVT. 2,4,9,10,12,13 Furthermore, other studies have found a correlation between the extent of LGE and inducible ventricular tachycardia (VT) and the origin of ventricular arrhythmia to be within the myocardium exhibiting LGE.…”
Section: Introductionmentioning
confidence: 99%
“…Имеющие-ся в настоящее время шкалы оценки риска ВСС у пациентов с ГКМП основываются на оценке анамнеза, результатах генетических исследова-ний, а также данных ЭхоКГ и ХМ ЭКГ [4]. По мнению многих авторов, наличие миокар-диального фиброза также может играть ключе-вую роль в формировании аритмий у пациен-тов с ГКМП [30]. следования показали, что пациенты с ГКМП и жизнеугрожающими аритмиями имеют высо-кую электрическую дисперсию и неоднород-ность внутрижелудочковых структур, что, веро-ятнее всего, связано с различием диаметра кардиомиоцитов, миокардиальным фиброзом, что тем самым образует субстрат для ЖА.…”
Section: рис 2 (unclassified
“…следования показали, что пациенты с ГКМП и жизнеугрожающими аритмиями имеют высо-кую электрическую дисперсию и неоднород-ность внутрижелудочковых структур, что, веро-ятнее всего, связано с различием диаметра кардиомиоцитов, миокардиальным фиброзом, что тем самым образует субстрат для ЖА. Интересные данные были получены при анализе взаимосвязи между степенью миокар-диального фиброза и возникновением ЖТ/ФЖ у больных ГКМП и подтвержденными мутациями саркомера TNNI3, MYBPC3 и MYH7 (30). По дан-ным Fujita T. с соавт.…”
Section: рис 2 (unclassified